Analisis Stabilitas Lereng Jalan di Kecamatan Wolasi Kabupaten Konawe Selatan Provinsi Sulawesi Tenggara - Laode Jonas Tugo; La Ode Sahidin; Ali Okto; Indrawati (Program Studi Teknik Geofisika FITK UHO, 2024)
The provincial road that stretches in Wolasi District, Matawolasi Village, South Konawe Regency, has hilly and mountainous topography. The road cuts through hillsides and mountains, resulting in the formation of a steep slope on one side of the road. Such conditions can pose a threat in the form of landslides or mass movement of rock/soil which can occur at any time. This research aims to analyze the characteristics of the rock mass and evaluate the stability of the road slope. To achieve the research objectives, several stages were carried out, namely field measurements, data processing (determining the type of landslide and empirical parameters) and slope stability analysis. The field measurement method used is the scanline method. The methods used to analyze slope stability are kinematic, analytical and Slope Stability Probability Classification (SSPC) methods. The research results show that the types of landslides at the observation station consist of plane landslides and wedge landslides. The probability value of slope stability at 10 observation station points is above 95%. This is confirmed by the results of the slope safety factor (FK) calculation which shows that the overall FK value of the slope is above 3.